2018
DOI: 10.12806/v17/i2/r3
|View full text |Cite
|
Sign up to set email alerts
|

Celebrities and slackers: A grounded theory of the dynamics of social loafing on student teams

Abstract: The purpose of this study was to explore how team members identify the social loafers on their teams and how they explain and manage social loafers' behavior. The participants (n=49) in the study included members of student teams participating in a service project as a part of their coursework. We collected multiple sources of information: in-depth interviews, reflection journals, peer evaluations, and observations of team members interacting. Using attribution theory and status characteristics theory we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Depending on these factors, the remaining team members may rather compensate for missing contributions, instead of reducing their own efforts (cf. Harding 2018;Williams and Karau 1991) or even pressuring the 'loafing' group members to contribute (Boren and Morales 2018;Freeman and Greenacre 2011). Note here, that the results by Freeman and Greenacre (2011) suggest that students may not be sensitive to the difference between students who contribute less due to a lack of competence instead of a lack of effort.…”
Section: Promoting Equal Participation -But Does It Even Matter?mentioning
confidence: 72%
See 2 more Smart Citations
“…Depending on these factors, the remaining team members may rather compensate for missing contributions, instead of reducing their own efforts (cf. Harding 2018;Williams and Karau 1991) or even pressuring the 'loafing' group members to contribute (Boren and Morales 2018;Freeman and Greenacre 2011). Note here, that the results by Freeman and Greenacre (2011) suggest that students may not be sensitive to the difference between students who contribute less due to a lack of competence instead of a lack of effort.…”
Section: Promoting Equal Participation -But Does It Even Matter?mentioning
confidence: 72%
“…At the core of the present study was the distribution of participation during web-based collaboration. Based on the numerous studies that consistently found unfavorable effects of unequal participation, social-loafing and free-riding behavior (Aggarwal and O'Brien 2008;Boren and Morales 2018;Capdeferro and Romero 2012;Freeman and Greenacre 2011;Goold et al 2008;Harding 2018;Johnson and Johnson 2009;Karau and Williams 1993;Kerr 1983;Khalil and Ebner 2014;Le et al 2018;Monzani et al 2014;Peñarroja et al 2017;Price et al 2006;Robert 2020;Williams and Karau 1991), our study was guided by the premise that equal participation during collaboration is beneficial for collaboration. We acknowledge that using the number of words as an indicator for participation might not be optimal.…”
Section: Promoting Equal Participation -But Does It Even Matter?mentioning
confidence: 99%
See 1 more Smart Citation
“…With social loafing interfering with this common intent for most students in their schooling, the use of different mechanisms to deal with such behavior within their groups is deemed crucial and necessary. This can be achieved through member confrontation to the social loafers (Zastrow, 2009), and reporting to instructors (Boren & Morales, 2018;Goo, 2011). Boren and Morales (2018) observed that member reactions to social loafers were determined by their status, with low status social loafers strictly being treated as per the rules established without further negotiations as opposed to high status social loafers.…”
Section: Theoretical Framework Literature Review and The Current Studymentioning
confidence: 99%
“…There is no doubt that all this is possible because of the employment of leadership and decision making skills among the group members. Therefore, training the students on the skills may facilitate their working in groups (Boren & Morales, 2018). The article has revealed three main approaches used by students to react to the social loafers each of which with their inherent drawbacks.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%